2020
DOI: 10.21203/rs.3.rs-127313/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Different Phenotypes and Chondrogenic Responses of Human Menstrual Blood and Bone Marrow Mesenchymal Stem Cells to activin A and TGF-β3

Abstract: Background: Due to its low capacity for self-repair, articular cartilage is highly susceptible to damage and deterioration, which leads to the development of degenerative joint diseases such as osteoarthritis. Menstrual blood-derived mesenchymal stem cells (MenSCs) are much less characterized compared to bone marrow mesenchymal stem cells (BMMSCs). However, MenSCs seem an attractive alternative to classical BMMSCs due to ease of access and broader differentiation capacity. The aim of this study was to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…27 Chondrogenic growth factors including TGF-β1, TGF-β3 and activin A. 169 Studies have shown that TGF-β1 may induce chondrogenic differentiation of BMSCs via the Smad 2/3 signaling pathway, leading to full-thickness AC regeneration. 170,171 Other studies reported that TGF-β1 signaling leads to Smad activation, directly enhancing the chondrogenic activity of AD-MSCs.…”
Section: Pro-chondrogenic Biomoleculesmentioning
confidence: 99%
“…27 Chondrogenic growth factors including TGF-β1, TGF-β3 and activin A. 169 Studies have shown that TGF-β1 may induce chondrogenic differentiation of BMSCs via the Smad 2/3 signaling pathway, leading to full-thickness AC regeneration. 170,171 Other studies reported that TGF-β1 signaling leads to Smad activation, directly enhancing the chondrogenic activity of AD-MSCs.…”
Section: Pro-chondrogenic Biomoleculesmentioning
confidence: 99%